Analisis Pendapatan Dan Alokasi Tenaga Kerja Dalam Upaya Pengembangan Usahatani Sutera Alam di Desa Krenceng Kecamatan Kepung Kabupaten Kediri - Afdah, Umi; Ananda, Chandra Farji; Fanani, Zaenal (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2024)
The objectives of this research are to identify: a) The contribution of income of natural silk farm  on household income; b) The contribution of labors alocation of natural silk farm on absorption of household labors; c) Factors affecting net income of natural silk farm; d) Factors effecting labors alocation on natural silk farm. This research conducted at Krenceng Village, Kepung Subdistrict, Kediri District, East Jawa. The result of this research shows that natural silk farm have any net income as much as Rp 1.256.963,19 per year, or give contribution of 31 percent on total household income. Total labor used on natural silk farm activities as much as 287,70 MDE per year, or have employe more than 28 percent of potential household labor force. Net income of natural silk farm influenced by farmer age, extent of farmer experience on natural silk farm, and extent of formal education. While price of eggs have negative impact on income of natural silk farm. Labor allocation on natural silk farm influenced by planting area of murbei, number of eggs, silk farm frequention and number of household members.